Computational analysis of TP53 vs. CTNNB1 mutations in hepatocellular carcinoma suggests distinct cancer subtypes with differential gene expression profiles and chromatin states. (December 2020) - Biterge Süt, Burcu
Graphical abstract: Highlights: TP53 and CTNNB1 are the top two most frequently mutated genes in HCC patients and are well-known drivers of tumorigenesis. TP53/CTNNB1 mutations occur almost mutually exclusively. Mutational status of TP53/CTNNB1 dictates significantly different gene expression signatures and chromatin states. As well as different prognostic outcomes and tumor infiltration levels. Abstract: Genetic variations are important drivers of carcinogenesis. It is extremely important to identify molecular distinctions between patients of the same disease for effective cancer treatment. This study aims to understand cellular and molecular differences between hepatocellular carcinoma patients carrying TP53 or CTNNB1 mutations, which could possess clinical significance. For this purpose, DNA sequencing and mRNA expression data for hepatocellular carcinoma patients were analyzed. Differentially expressed genes and the cellular processes that they are involved in were determined for TP53/CTNNB1-altered patient groups. We found that the mutations of TP53/CTNNB1 genes in the patient cohort was almost mutually exclusive and gene expression profiling in these subgroups were unique. Gene Ontology (GO) enrichment analysis of the differentially expressed genes identified several important cellular processes. In line with this, selected histone variants, histone chaperons, as well as the binding partners of TP53/CTNNB1 showed distinct enrichment levels. TP53/CTNNB1-altered patient groups laso showed different prognostic outcomes and tumor infiltration levels. In conclusion, our results strongly imply differential chromatin states and transcriptional regulation in relation to the mutational status of TP53 vs. CTNNB1, suggesting that these genes might be inducing different cellular pathways involving distinct chromatin environments during the course of carcinogenesis.